Study on the construction deformation of a slotted shield in loess tunnels with different buried depths and large sections - Jiang, Han; Fang, Xiaolong; Yu, Ming; Li, Lin; Han, Bing; Gao, Song; Zhai, Chengxian; Gao, Renxin; Zhao, Jianxiong; Liu, Liu (Frontiers in Earth Science, 2023)
Since there is no precedent for the use of slotted shield tunneling in the large section of high-speed railways in China, the relevant technological accumulation and systematic research achievements are few. Therefore, this paper provides theoretical support for loess tunnel construction decision-making through the study of slotted shields and is expected to promote the mechanization and even intelligent construction of a high-speed iron-loess tunnel. Taking the Luochuan tunnel of the Xiyan high-speed railway as the engineering background, this paper uses the numerical simulation software packages of ANSYS and FLAC3D to study the tunnel deformation (surface settlement, vault settlement, tunnel bottom uplift, and horizontal convergence) caused by the slotted shield construction in three different buried depths of 30, 40, and 50 m surrounding rock. The deformation law and mechanical characteristics of a cutter shield construction of large cross-section loess tunnels under the influence of different buried depths are put forward. Results showed that 1) the mutual interference between the working procedures can be significantly reduced by inserting the cutting tool into the soil instead of the advanced tubule before excavation; 2) the settlement in the upper part of the longitudinal axis of the tunnel is the largest; the greater the depth of the tunnel is, the smaller the surface settlement is; and 3) the horizontal deformation of the arch waist and foot of the tunnel under different buried depths is symmetrically distributed into the tunnel during the whole process of slotted shield tunneling.